Two Classes of Highly Similar Coiled Coil-Nucleotide Binding-Leucine Rich Repeat Genes Isolated from the Rps1-k Locus Encode Phytophthora Resistance in Soybean - Hongyu Gao; Narayanan N. Narayanan; Lori Ellison; Madan K. Bhattacharyya (Molecular Plant-Microbe Interactions, 2005)
A series of single genes protect soybean from the root and stem disease caused by the oomycete pathogen Phytophthora sojae. In the last two decades, Rps1-k has been the most stable and widely used Phytophthora resistance gene for the major soybean-producing regions of the United States. Four highly similar genes encoding coiled coil-nucleotide binding-leucine rich repeat (CC-NB-LRR)-type proteins were isolated from the Rps1-k locus. These genes were grouped into two classes based on their sequence identity. Class I contains three genes with identical open reading frames (ORF) and 5′ end regions. Two of these genes were also identical at the 3′ untranslated regions; the third gene showed a recombination breakpoint in the 3′ untranslated region resulting in the combination of 3′ end sequences of members from both classes. Reverse transcription-polymerase chain reaction analyses suggested that members of both classes of genes are transcribed at low levels. Representative members from each gene class were expressed in transgenic soybean plants. Analyses of independent R0, R1, R2, and R3 progeny populations suggested that both gene classes confer Phytophthora resistance in soybean. A possible evolutionary mechanism for the Class I gene family is proposed.